The impact of religiosity and financial literacy on financial management behavior and well-being among Indonesian Muslims - Wijaya, Haykal Rafif; Hijrah Hati, Sri Rahayu; Ekaputra, Irwan Adi; Kassim, Salina (Springer Nature, 2024)
This study examines the effects of religiosity and Islamic financial literacy on Muslims’ financial behavior and well-being. Additionally, it investigates the impact of sociodemographic variables on the centrality of religiosity, financial literacy, financial management behavior, and the well-being of Muslim consumers. This research integrates perspectives from Rational Choice Theory, the Rational Choice Theory of Religion, and Behavioral Finance to illuminate the mechanisms behind these relationships. Data were collected through a nonprobability sampling method from 1141 Muslim individuals aged between 18 and 65 living in Indonesia. The results indicate that the centrality of religion in the lives of Muslim consumers and Islamic financial literacy significantly affects their financial management behavior and financial well-being. However, the empirical evidence suggests a more substantial effect of Islamic financial literacy than religiosity on both dependent variables.